2015
DOI: 10.1159/000434749
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Positivity in Women Undergoing Intrauterine Insemination Has a Negative Effect on Pregnancy Rates

Abstract: Background: Sexually transmitted infections are a major cause of infertility. Human papillomavirus (HPV) infection is one of the most common viral infections of the female genital tract. Only a limited number of studies have investigated the influence of HPV on fertility and its impact remains controversial. Objective: We investigated the relationship between cervical HPV infection and pregnancy outcome after intrauterine insemination (IUI). Since other sexually transmitted infections could also influence outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Five studies [17, 18, 21, 23, 31] reported the risk of sPTB and 7 studies [10-12, 19-22] reported the risk of clinical pregnancy rate of ART. Eight studies [12, 17, 18, 20, 21, 23, 27, 29] reported HR-HPV infection alone and the other 10 studies [10, 11, 19, 22, 24-26, 28, 30, 31] reported indiscriminate genotype infection (HR/LR-HPV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies [17, 18, 21, 23, 31] reported the risk of sPTB and 7 studies [10-12, 19-22] reported the risk of clinical pregnancy rate of ART. Eight studies [12, 17, 18, 20, 21, 23, 27, 29] reported HR-HPV infection alone and the other 10 studies [10, 11, 19, 22, 24-26, 28, 30, 31] reported indiscriminate genotype infection (HR/LR-HPV).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained upon stratified analyses of prospective cohort studies [10-12, 19] and retrospective cohort studies [20-22], with RRs being 1.30 (95% CI 0.61–2.80; I 2 = 82.5%) and 0.82 (95% CI 0.37–1.81; I 2 = 69.1%) respectively (Table 2). Of the 7 studies, 3 studies [12, 20, 21] reported infection with HR-HPV alone and the other 4 studies [10, 11, 19, 22] reported mixed-type infection with HR/LR-HPV, with pooled RRs of 1.66 (95% CI 0.29–9.63; I 2 = 90.7%) and 0.85 (95% CI 0.66–1.09; I 2 = 20.2%) respectively (Table 2). In addition, 5 studies [12, 19-22] reported the risk of HPV infection on spontaneous abortion of ART pregnancy, with the pooled RR being 1.47 (95% CI 0.86–2.50; I 2 = 12.9%).…”
Section: Resultsmentioning
confidence: 99%
“…Detectable HPV infection among males has been associated with reduced sperm motility, increased antisperm antibodies, and lower pregnancy rates in studies of infertile couples; another study found no effect on semen quality . Among females undergoing intrauterine insemination, 1.9% with detectable HPV infection conceived compared with 11.4% without the virus . Surgical treatment for HPV‐associated cervical dysplasia may also influence fertility.…”
mentioning
confidence: 99%
“…Its footprint on the scientific world is widespread, including use for diagnostics in the clinical laboratory, immunodetection of biologically relevant molecules in the basic science research laboratory, and even in pregnancy tests as part of our daily lives (Tsujii et al, 1998; Lyer et al, 2015; Santaclara et al, 2015; Depuydt et al, 2015). ELISAs are used for diagnosis or detection of allergic responses (insect stings, indoor allergens, food, latex), communicable diseases (HIV, ebola, lyme disease, chagas disease, rocky mountain spotted fever, leishmasiasis), and endocrine disorders (hyper- and hypothyroidism).…”
Section: Introductionmentioning
confidence: 99%